Odpowiedzi

2010-02-02T15:48:30+01:00
3x-4=2y-5
3y-9=x+3

3x-4=2y-5
x=3y-12

3(3y-12)-4=2y-5
x=3y-12

9y-36-4=2y-5
x=3y-12

9y-2y=-5+36+4
x=3y-12

7y=31+4
x=3y-12

7y=35
x=3y-12

y=5
x=3




x=y+1
2x=5x-4y

x=y+1
-3x=-4y

x=y+1
-3(y+1)=y+1

x=y+1
-3y-3=y+1

x=y+1
-4y=4

x=y+1
y=-1

x=0
y=-1
1 5 1
  • Użytkownik Zadane
2010-02-02T15:49:10+01:00
3x-4=2y-5
3y-9=x+3

3x-4=2y-5
x=3y-12

3(3y-12)-4=2y-5
x=3y-12

9y-36-4=2y-5
x=3y-12

9y-2y=-5+36+4
x=3y-12

7y=31+4
x=3y-12

7y=35
x=3y-12

y=5
x=3
__________________
x=y+1
2x=5x-4y

x=y+1
2x-5x=-4y

x=y+1
-3x=-4y

x=y+1
-3*(y+1)=-4y

x=y+1
-3y-3=-4y

x=y+1
-3y+4y=3

x=y+1
y=3

x=3+1
y=3

x=4
y=3
1 5 1